Cleaners and labourers on Facebook? Bulgarians in the UK between free movers and a digital diaspora. Issue 13 (3rd October 2022) - Nancheva, Nevena
ABSTRACT: This study explores the way Bulgarians living in the UK interact online. We rely on an online survey of attitudes among Bulgarians in the UK, participant observation in Bulgarian support networks during the period 2016-20, as well as qualitative interaction analysis over the course of six months (2019-20), adapted for non-visual environments, of top posts from the largest online support groups. Our findings point to the gradual consolidation of organised informal support among Bulgarians, especially and predominantly among those of 'low-status' occupations and more precarious migration journeys. We also observe a trend of emancipation and entrepreneurship enabled by online networks in the almost complete absence of formal associations of Bulgarians in the UK. Finally, we acknowledge the importance of the context of crisis and precarity for the emergence of informal support networks online. What this tells us about Bulgarians in the UK is that, while often avoided by so called 'elite migrants', informal support groups have begun to function as quasi-diasporic communities assisted by online social networking platforms, (still) facilitated by free movement but creating a unique transnational space between 'home' and 'the foreign' to enable mobility, interaction and belonging.